Powers of nostalgia: Ollanta and the neo-Inca movement - Cordiviola, Alfredo (Universidad Pedagógica y Tecnológica de Colombia, 2010)
This essay analyzes the indigenous rebellions and its evolution in Perú during the XVIII century as well as the functions and impact that nostalgia and utopia had against the mastery of Spanish, keeping in mind that both, nostalgia and utopia, were used like instruments against this movement. The uprising increases due to the abuse of power and the constant inequalities of imperial economy in and around the viceroyalty based on specific unions between social actors. By the year 1780, they conformed a group called broad Inca nationalist movement whose clear expression was showed in the insurrection promoted by Tupac Amaru. We are going to present the possible interpretations to study the evolution of this movement through this project which is related to the history context OLLANTAY. Simultaneously we are going to take advantage of it in order to analyze other texts and arts.